Agar Gradient Diffusion Susceptibility Testing for Neisseria gonorrhoeae: A Reliable Alternative to Agar Dilution?. (4th October 2017) - Desjardins, Michaël; Lefebvre, Brigitte; Labbé, Annie-Claude; Martin, Irene; Mauffrey, Florian; Longtin, Jean; Fortin, Claude
Abstract: Background: Antimicrobial susceptibility testing by agar dilution, the gold-standard for determination of minimal inhibitory concentration (MIC) for N. gonorrhoeae, is a labor intensive technique usually performed in reference laboratories. Agar gradient diffusion is a simpler alternative to obtain MICs. However, correlation of N. gonorrhoeae MIC values obtained by the two methods is not well established. The objective of this study is to evaluate performance of agar gradient diffusion compared with agar dilution for N. gonorrhoeae . Methods: Fifty strains of N. gonorrhoeae (34 isolates from clinical specimens; 14 WHO reference and two ATCC strains), all confirmed to be genetically distinct using molecular typing (NG-MAST), were selected. Isolates with known high MICs were targeted. Agar gradient diffusion MIC testing was done in a clinical laboratory on all strains for ceftriaxone, cefixime, and azithromycin while comparing two different commercial antimicrobial strips (bioMérieux, Alere) on three different culture media (BD, Oxoid, CLSI's recommended medium). Agar dilution MIC testing according to CLSI was done at the Québec provincial reference laboratory on all strains. Performance of agar gradient diffusion was assessed by accuracy, using essential and categorical agreements, and by precision (reproducibility). Results: When comparing agar dilution and agar gradient diffusion using bioMérieux strips on CLSI testing medium, essential agreements (within 1-log2 dilution) were 94, 88, and 82% for ceftriaxone, cefixime, and azithromycin, respectively. Categorical agreements were 100, 94, and 94%. Agar gradient diffusion, compared with agar dilution, had a tendency to under-estimate MIC for third-generation cephalosporins, not classifying 86% of isolates with decreased susceptibility (MIC 0.12–0.25 mg/l for ceftriaxone, 0.25 mg/l for cefixime) as such. Overall precision of agar gradient diffusion was 96%. Conclusion: Agar gradient diffusion using bioMérieux strips on CLSI testing medium shows satisfactory accuracy compared with agar dilution for N. gonorrhoeae MIC testing of third-generation cephalosporins and azithromycin even in a carefully selected panel of strains. Disclosures: M. Desjardins, bioMerieux: Research Contractor, Research support. BD: Research Contractor, Research support. Alere: Research Contractor, Research support. Oxoid: Research Contractor, Research support. C. Fortin, Alere: Research Contractor, Research support. bioMerieux: Research Contractor, Research support. BD: Research Contractor, Research support Oxoid: Research Contractor, Research support